COMMUNITY DEVELOPMENT THROUGH VILLAGE PARIGI LOCAL RESOURCE UTILIZATION - Agustinus, Candra (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2016)
Activity Real Working Lecture (KKN) Faculty of Islamic economy in 2016 is onemanifestation of Panca Dharma College University Djuanda namely Community devotion. Asfor the object of corruption are the 2016 FEI Society Kp. Parigi Tangkolo Rural Developmenttheme Kabandungan with Sharia-based economic activity. No action whithout goal.Therefore, the purpose of the Student FEI KKN is to be a facilitator for the community insolving social and economic problems by optimizing natural resources and human resources,especially people in the Kp. Tangkolo Parigi. Results of the 2016 FEI corruption can besimply summed have found the local potential in the natural surroundings and take positiveaction against such potential, namely the processing of agricultural products and the field ofnature conservation eggplant. Hopefully, by the development of the processing ofagricultural products, we can improve the HDI (Quality Performance Index) especiallycomponents perekonomi surrounding communities.